Desenvolvimento pós-embrionário do intestino médio de Dermatobia hominis (Linnaeus Jr.) (Diptera, Cuterebridae) - Lello, Edy de [UNESP]; Vieira, Ana Maria (Sociedade Brasileira de Zoologia, 2001)
Dermatobia hominis (Linnaeus, 1781) midgut is internally lined by an epithelium of polytenic cells, some low others prismatic with well developed brush border. Their apical portion are enlarged by secretory vesicles, forming button-like structures that are pinched off to the lumen, some accompained by the nucleus characterizing apocrine and holocrine secretions. This epithelium is gradually renewed by small, non polytenic regenerative cells, found scattered at its basal portion. At the end of the third instar the metamorphosis begins. The epithelial cells present signs of degeneration and at the first day of pupation the regenerative cells increase in number. By the 5th day of pupation these regenerative cells, besides being increased in number, differentiate themselves into two layers: one similar to the dense conective tissue that sustainning the larval epithelium is pinched off to the midgut lumen forming the yellow bodies; the other, develops right under it as the imaginal epitelium. The disorganized muscles bundles of the midgut wall, are invaded by phagocytes. At the end of pupation the midgut has a low prismatic epithelium with brush-border. In the adult, the torax portion of the midgut has prismatic homogeneously basophilic epithelium while in the abdominal portion the epithelium is made of high prismatic cells full of small vacuoles. The larval midgut epithelium suffers programmed cell death non compatible with apoptose. During the metamorphosis the midgut lenght diminishes from 31mm in the larva to 14mm in the adult.
Post-embryonic development of Dermatobia hominis (Linnaeus Jr.) (Diptera, Cuterebridae) midgut
Keywords: Diptera; Dermatobia hominis; midgut; metamorphosis; histology; post-embryonic development